2018
DOI: 10.18203/2319-2003.ijbcp20185123
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of a fixed dose combination of paracetamol, chlorpheniramine maleate and phenylephrine in treatment of common cold: a phase IV, open-labelled, multi-centric study

Abstract: Background: Acute coryza or common cold affects the upper airways, sometimes in association with low-grade fever and systemic symptoms, and usually presents with at least two of the following symptoms: cough, dysphonia, throat discomfort, sore throat, nasal congestion, rhinorrhoea, sneezing, headaches, myalgia and fever. A triple combination of analgesics, decongestants and antihistamines provides better relief for multiple symptoms in common cold and allergic rhinitis according to various studies. A combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…(3) Common cold is a self-limiting disease so the treatment should focus on symptomatic relief as there is no effective antivirals for the treatment of common cold. (4) Optimum symptomatic relief from the single drug therapy is not possible which is why the combination therapy is always preferred by the healthcare professionals for the symptomatic treatment. As per the Cochrane review, guidelines of DPHHS, Picon PD et al and Eccles R et al the combination of antihistamines, decongestants and analgesics can provide significant symptomatic relief in common cold.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Common cold is a self-limiting disease so the treatment should focus on symptomatic relief as there is no effective antivirals for the treatment of common cold. (4) Optimum symptomatic relief from the single drug therapy is not possible which is why the combination therapy is always preferred by the healthcare professionals for the symptomatic treatment. As per the Cochrane review, guidelines of DPHHS, Picon PD et al and Eccles R et al the combination of antihistamines, decongestants and analgesics can provide significant symptomatic relief in common cold.…”
Section: Introductionmentioning
confidence: 99%
“…A Total of 16.57 % patients experienced adverse events majority being sedation and drowsiness which could be due to Chlorpheniramine maleate. The study concluded that the combination of Paracetamol, Phenylephrine and Chlorpheniramine maleate was efficacious and safe for the treatment of common cold and allergic rhinitis [12] .…”
Section: Discussionmentioning
confidence: 99%
“…(3) The drawback of the research was that a common cold is a self-limiting disease and can be naturally cured in 10 days as per the literature. (7,8) So to minimize the same, the clinical trial duration was kept 5 days so the maximum efficacy results presented in this paper were considered to be because of the investigational product.…”
Section: Discussionmentioning
confidence: 99%